Prediction of elastic material properties in additively fabricated multimaterials (Transactions on Additive Manufacturing Meets Medicine, 2021)
The use of multimaterial 3d printers allow not to only shape the geometry but also the material properties of the part being designed. The difficulty for the designer is now to anticipate, what the resulting material properties of the mixture might be. Here a continuum mechanical approach is presented, and how this can be applied to currently used multimaterial printers using photopolymers and its use in a digital design process.
Keywords: additive manufacturing; multiscale continuum micromechanics; multi-material jetting